Ruthenium Complexes: An Alternative to Platinum Drugs in Colorectal Cancer Treatment - Kazi Mustafa Mahmud; Mahruba Sultana Niloy; Md Salman Shakil; Md Asiful Islam (MDPI AG, 2021)
Colorectal cancer (CRC) is one of the intimidating causes of death around the world. CRC originated from mutations of tumor suppressor genes, proto-oncogenes and DNA repair genes. Though platinum (Pt)-based anticancer drugs have been widely used in the treatment of cancer, their toxicity and CRC cells' resistance to Pt drugs has piqued interest in the search for alternative metal-based drugs. Ruthenium (Ru)-based compounds displayed promising anticancer activity due to their unique chemical properties. Ru-complexes are reported to exert their anticancer activities in CRC cells by regulating different cell signaling pathways that are either directly or indirectly associated with cell growth, division, proliferation, and migration. Additionally, some Ru-based drug candidates showed higher potency compared to commercially available Pt-based anticancer drugs in CRC cell line models. Meanwhile Ru nanoparticles coupled with photosensitizers or anticancer agents have also shown theranostic potential towards CRC. Ru-nanoformulations improve drug efficacy, targeted drug delivery, immune activation, and biocompatibility, and therefore may be capable of overcoming some of the existing chemotherapeutic limitations. Among the potential Ru-based compounds, only Ru (III)-based drug NKP-1339 has undergone phase-Ib clinical trials in CRC treatment.